2009
DOI: 10.1093/bja/aen382
|View full text |Cite
|
Sign up to set email alerts
|

Advance of age decreases the minimum alveolar concentrations of isoflurane and sevoflurane for maintaining bispectral index below 50

Abstract: Advance in age significantly decreased the concentrations of isoflurane and sevoflurane required to maintain BIS below 50. BIS correctly reflected age-associated decrease of end-tidal concentrations of isoflurane and sevoflurane required for maintaining adequate depth of anaesthesia during resting state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
36
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 16 publications
8
36
1
1
Order By: Relevance
“…9 Furthermore, compared with young people, the concentration required to attain the similar anesthetic depth, either intravenous or inhaled anesthetics, is decreased in elderly patients. 17,18 Similar to other investigators, 6e8 we also found women wakened faster from general anesthesia than men, even in cardiac surgery, which belongs to the more complex procedures. Gan et al discovered that gender appeared to be an independent predictor for recovery time.…”
Section: Discussionsupporting
confidence: 89%
“…9 Furthermore, compared with young people, the concentration required to attain the similar anesthetic depth, either intravenous or inhaled anesthetics, is decreased in elderly patients. 17,18 Similar to other investigators, 6e8 we also found women wakened faster from general anesthesia than men, even in cardiac surgery, which belongs to the more complex procedures. Gan et al discovered that gender appeared to be an independent predictor for recovery time.…”
Section: Discussionsupporting
confidence: 89%
“…In the pediatric literature, evidence documenting the effectiveness of sevoflurane inhalation is limited to a single case report describing a 3-month-old boy presenting with post-extubation status asthmaticus (11). This young patient received sevoflurane at anesthetic doses of 2-3% (the minimum alveolar sevoflurane concentration for loss of consciousness is 3.2 +/-0.1% at 1-6 months of age, with no gender differences) (12).…”
Section: Discussionmentioning
confidence: 99%
“…End-inspiratory concentration was adjusted at the predetermined value according to the “up-down” method described by Dixon and Mood. [9] Patients received 1.2% end-inspiratory isoflurane (approximately 1 minimum alveolar concentration [MAC]) of isoflurane[10] in the control group and 0.6% end-inspiratory isoflurane (approximately 0.5 MAC) of isoflurane in the dexmedetomidine group. [10] These initial isoflurane concentrations were chosen based on previous studies in which similar dexmedetomidine doses decreased isoflurane requirements for anesthetic maintenance by 25-90%.…”
Section: Methodsmentioning
confidence: 99%
“…[9] Patients received 1.2% end-inspiratory isoflurane (approximately 1 minimum alveolar concentration [MAC]) of isoflurane[10] in the control group and 0.6% end-inspiratory isoflurane (approximately 0.5 MAC) of isoflurane in the dexmedetomidine group. [10] These initial isoflurane concentrations were chosen based on previous studies in which similar dexmedetomidine doses decreased isoflurane requirements for anesthetic maintenance by 25-90%. [1112] The predetermined end inspiratory concentration of isoflurane was maintained for at least 15 min to allow adequate time for alveolar and brain isoflurane partial pressures to equilibrate.…”
Section: Methodsmentioning
confidence: 99%